Self-Assessment System: Detrimental Effects upon Entrepreneurial and Innovative Activity - KOTNIK, Patricia; KOVAČ, Mitja (Journal of Advanced Research in Law and Economics; Vol 5 No 1 (2014): JARLE, Volume V, Issue 1(9), Summer 2014, 2017)
Efficient regulatory mechanisms that induce innovation, co-operation and deter competition law infringements have recently been the subject of growing attention. Competition is essential to the innovation process which in general terms enables entrepreneurship. But so too is co-operation between firms which requires an exchange of information and may lead to inefficient collusive behavior. The optimal trade-off between the provision of stable entrepreneurial incentives and the new European competition law’s reform with the self-assessment system has been largely missing from the current scholarly debate. This paper identifies the unintended horizontal side effects of this new self-assessment system upon the entrepreneurial activity, offers a legal evaluation of the optimal entrepreneurial incentive mechanisms and provides legal and Economics arguments for an improved regulatory response.